1993
DOI: 10.21273/jashs.118.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Physicochemical Changes during Maturation and Postharvest Storage of Muskmelon Fruit

Abstract: Changes in the physical and chemical properties of the plasma membrane from hypodermal mesocarp tissue of netted muskmelon (Cucumis melo L. var. reticulatus Naud.) fruit were compared in relation to the permeability changes of the same tissue during fruit maturation and storage at 4 or 24C. As muskmelon fruit progress from immaturity to maturity, and with storage of mature fruit at 4 or 24C, increased permeability of the hypodermal-mesocarp tissue occurs coincident with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 0 publications
1
34
0
3
Order By: Relevance
“…Kiwifruit is a potential source of SOD with unusual properties. Many reports have shown that SOD activity is significantly different in different fruit cultivars, in different periods of fruit development, in different parts of the fruit, as well as over different storage times [34][35][36][37][38][39]. The present work determined the SOD activity in eight genotypes of Actinidia.…”
Section: Vitamin C and Total Sod Activitymentioning
confidence: 87%
“…Kiwifruit is a potential source of SOD with unusual properties. Many reports have shown that SOD activity is significantly different in different fruit cultivars, in different periods of fruit development, in different parts of the fruit, as well as over different storage times [34][35][36][37][38][39]. The present work determined the SOD activity in eight genotypes of Actinidia.…”
Section: Vitamin C and Total Sod Activitymentioning
confidence: 87%
“…The free radicals disrupt normal metabolism through peroxidating lipids, denaturing proteins and nucleic acids (Jiang and Zhang, 2001;Bor et al, 2003). Lipid peroxidation causes degradation and impairment of structural components (Lester and Stein, 1993). This leads to change in selective permeability of bio-membranes (Weckx and Clijsters, 1997) and thereby membrane leakage and change in activity of enzymes bound to membrane (Lester and Stein, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation causes degradation and impairment of structural components (Lester and Stein, 1993). This leads to change in selective permeability of bio-membranes (Weckx and Clijsters, 1997) and thereby membrane leakage and change in activity of enzymes bound to membrane (Lester and Stein, 1993). These hasten the loss of membrane integrity and cell metabolites such as sugar, protein, phenols etc (Lott et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The emerging model for chilling injury is of membrane lipids undergoing biophysical and chemical changes that lead to a cascade of biochemical reactions culminating in cell death and tissue deterioration ( Marangoni et al 1996 ). Because these events also occur in ripening/ senescing tissues ( Lester & Stein 1993; Lacan & Baccou 1996, 1998), it has been hypothesized that the plant hormone ethylene could play a role in the triggering of chilling injury. Earlier studies had already documented that some climacteric and non‐climacteric fruit were more sensitive to chilling when treated with ethylene ( Wang 1993; Yuen et al 1995 ).…”
Section: Introductionmentioning
confidence: 99%